A linear-algebraic method to compute polynomial PDE conservation laws. (January 2022) - Boreale, Michele; Collodi, Luisa
Abstract: We present a method to compute polynomial conservation laws for systems of partial differential equations (PDE s). The method only relies on linear algebraic computations and is complete, in the sense it can find a basis for all polynomial fluxes that yield conservation laws, up to a specified order of derivatives and degree. We compare our method to state-of-the-art algorithms based on the direct approach on a few PDE systems drawn from mathematical physics.